Field programmable gate array implementation of a single‐input fuzzy proportional–integral–derivative controller for DC–DC buck converters. Issue 6 (1st May 2016) - Chang, Changyuan; Yuan, Yubo; Jiang, Tianlin; Zhou, Zhongjie
Abstract : The design and field programmable gate array implementation of a single‐input fuzzy (SIF) proportional–integral–derivative (PID) control scheme applied to DC–DC buck converters are presented. The SIF logic reduces the number of fuzzy rules and therefore the hardware resource occupancy without control property degradation compared with the double‐input fuzzy (DIF) controller, which is realised by transforming the two‐dimension rule tables into one‐dimension rule vectors using signed distance method and genetic algorithm. The adopted signed distance method requires the two‐dimension rule tables to be of Toeplitz structure, which is realised by establishing the inference rules through analysing the system response curve. The fuzzy logic regulates the PID parameters based on the conditions of the power converters. As a result, the SIF‐PID controller is superior to the conventional PID controller and is similar to DIF‐PID controller in terms of the control performance. The proposed controller has been validated with simulation and experimental results.